2012
DOI: 10.1159/000330920
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Ultrasound Demonstrates Variable Location of the Intercostal Artery

Abstract: Background: Ultrasound (US) guidance is advocated to reduce complications from thoracocentesis or intercostal catheter (ICC) insertion. Although imaging of the intercostal artery (ICA) with Doppler US has been reported, current thoracic guidelines do not advocate this, and bleeding from a lacerated ICA continues to be a rare but serious complication of thoracocentesis or ICC insertion. Objectives: It was the aim of this study to describe a method to visualise the ICA at routine US-guided thoracocentesis and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 44 publications
1
31
0
1
Order By: Relevance
“…SALAMONSEN et al [101] visualised intercostal arteries using colour Doppler and confirmed significant variation in their course. In a subsequently contrast CT-validated study, ultrasound had excellent sensitivity (86%) but poor specificity (30%) for detecting such vulnerable intercostal vessels [102].…”
Section: Chest Wall Abnormalitiesmentioning
confidence: 88%
“…SALAMONSEN et al [101] visualised intercostal arteries using colour Doppler and confirmed significant variation in their course. In a subsequently contrast CT-validated study, ultrasound had excellent sensitivity (86%) but poor specificity (30%) for detecting such vulnerable intercostal vessels [102].…”
Section: Chest Wall Abnormalitiesmentioning
confidence: 88%
“…While most physicians use ultrasound merely to mark the site for needle insertion before setting up for the procedure, real-time ultrasound using a sterile sleeve allows sampling of previously unreachable small loculated effusions and occasionally allows parietal pleural biopsies. Furthermore, recent evidence suggests that pre-procedural identification of the intercostal artery, the course of which can be unpredictable, is easily achieved with a high-frequency probe and could help avoid rare but potentially fatal bleeding complications 2022 . Ultrasound examination immediately after the procedure can indirectly suggest the occurrence of pneumothorax by the disappearance of the typical “sliding” sign, representing the sliding of visceral and parietal pleura over each other.…”
Section: Diagnosis Of Pleural Diseases: Non-invasive Studiesmentioning
confidence: 99%
“…US enables visualization of the course of an aberrant or intercostal vessel which is advantageous to determine the best location for drain insertion. It is well known that more vulnerable intercostal arteries are found near the spine, disappearing gradually behind the overlying rib in the axillar plane [25]. A sensitivity of 86% for US to detect vessels within the intercostal space was demonstrated in a study in 50 patients [26].…”
Section: Us and Pleural Effusionmentioning
confidence: 99%